Foresight analysis as an innovation policy tool : a socio-economical approach - Moniz, António Brandão (2001)
At the last National Conference of Industrial Sociology in Portugal (in March 1999) was presented a paper on the topic of “foresight as a technology and employment policy instrument” (A.B. Moniz) where there was a reference to the need of development of this kind of tools and instruments. This need is clear when one should neutralize the negative effects of such policies, and could support the positive influences, especially with the main aims of improvement of quality of working life. Thus, is today possible to make a first balance of the application in Portugal of a type of foresight analysis exercise: the Delphi method. After some of the uses of this method in Portugal on the fisheries socio economical system and on the relation between information society and employment, we present in this paper a first assessment of such experiments and present some recommendations for future uses of this foresight technique. We conclude that they must be applied within the context of socio-economical perspectives, and not only the technological ones, although they should include that dimension.